2014
DOI: 10.1007/s40009-013-0205-4
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Effect of Kharif Crops on Phosphatases and Dehydrogenase Activities in a Typic Haplustert

Abstract: In recent years phosphorus crisis is emerging at global level, every country in the world searching for alternative sources and management options for increasing its supply and use efficiency. Increasing cost of cultivation due to phosphatic fertilizers, attracting our mind towards it. In this experiment it was focused on effect of major kharif crops (maize, soybean, sorghum, pearl millet, finger millet and rice) on phosphatases and dehydrogenase activities in soil at different crop growth periods (30, 50, 75,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…Apparently, rhizosphere phosphatase and dehydrogenase activity tends to be higher because of increased microbial numbers in the rhizosphere and the excretion of plant root enzymes. These enzyme activities associated with higher availability and uptake of nutrients, particularly phosphorus in plants (Šarapatka, 2002 andDotaniya et al, 2014).These results are in the same line with previous studies confirming a positive impact of rhizobia with PGPR and AM-fungi activities on soil quality by increasing the activity of soil enzymes (Prasad et al, 2012;Othman andTamimi 2016& Mouradi et al, 2018).…”
Section: Dehydrogenase and Phosphatase Activitiessupporting
confidence: 87%
“…Apparently, rhizosphere phosphatase and dehydrogenase activity tends to be higher because of increased microbial numbers in the rhizosphere and the excretion of plant root enzymes. These enzyme activities associated with higher availability and uptake of nutrients, particularly phosphorus in plants (Šarapatka, 2002 andDotaniya et al, 2014).These results are in the same line with previous studies confirming a positive impact of rhizobia with PGPR and AM-fungi activities on soil quality by increasing the activity of soil enzymes (Prasad et al, 2012;Othman andTamimi 2016& Mouradi et al, 2018).…”
Section: Dehydrogenase and Phosphatase Activitiessupporting
confidence: 87%
“…The research findings confirmed with Dotaniya et al, (2014) observed that different crop growth stages showed different amount of dehydrogenase activity in soil, it might be due to secretion of root exudates and biochemical changes in plant system. More microbial activities increased the Dehydrogenase enzymatic activity in the rhizosphere, due to more availability of food materials for its growth.…”
Section: Dehydrogenasesupporting
confidence: 85%
“…The results supported by the findings of Naseby et al, (2000) stated that the acid phosphatase activity was more dependent upon the nutritional status of the plant. Dotaniya et al, (2014) confirmed that different crop growth stages showed different amount of acid phosphatase activity, it might be due to secretion of root exudates and biochemical changes in plant system. Similar findings confirmed by Kaleeswari (2007).…”
Section: Acid Phosphatasementioning
confidence: 62%
“…The potential activity of β-glucosidase in studied arable field showed significant seasonal changes patterns and was significantly higher in April than in August in both study years. Seasonal variation of enzymatic activity could be associated with the different stages of plant growth (Dotaniya et al 2014). In our study, increased BG activity was observed during the intensive growth of winter wheat (April 2007) and winter rape (April 2008).…”
Section: Discussionsupporting
confidence: 50%